Preparation and professional development of secondary school principals’ leadership in Henan Province, China / Jiang Na - Jiang, Na (2017)
Principal preparation and training is the key to school and system improvement. This study was intended to investigate the preparation and professional development of secondary school principals’ leadership in Henan Province, China. It allows for a deeper understanding of the current status of the school principals’ preparation and professional development and aims to develop constructive suggestions in improving the current status and resolving the constraints of this effort. Data was collected through open-ended questionnaires and semi-structured interviews with the secondary school principals and training providers. Observations of school principals’ routine work and training programs were also conducted to support the research findings. Thirty-seven school principals participated in an open-ended survey, seventeen school principals were interviewed and six training providers were selected from different training institutes to share their experiences and perceptions in three areas: (1) the ways they prepare for their roles; (2) the challenges and constraints of their preparation and professional development; (3) the challenges and constraints of their leadership practices. All interviews were recorded digitally and fully transcribed. Inductive coding was employed, to reduce, simplify and transform the data to facilitate data analysis. A classification of themes was then undertaken and emerging patterns were verified and confirmed. This case study outlines the findings by way of triangulating the data sets. The findings of this research study highlighted various shortcomings of policy implementation and standards, accompanied with some contradictions associated with the current demands of the principal’s role in meeting these demands. This research presented the following recommendations in support of policy implementation: (1) Principals’ professional development policy construction, (2) Promotion of formal and informal learning, (3) Resolving challenges in preparing and developing professionalism, and (4) Solving constraints in principal leadership practices. It is with the hope that the proposed suggestions derived through this study, can be a merit in enhancing educational policies to facilitate the educational reform, as a stepping stone for further research in this area of study.